Madagascar : Third Review Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Madagascar showed satisfactory performance under the Poverty Reduction and Growth Facility (PRGF) program. Executive Directors agreed that the crisis has undermined the timely achievement of the program, requiring the government to redouble its efforts. They welcomed the 2003 budget and stressed the need for strengthening fiscal and monetary policies and accelerating structural reforms. They urged the need to address the problems of inefficiency and corruption in the public administration. They emphasized the need to decisively implement the strategy, and successfully complete the third review under the PRGF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet